The Effectiveness of the Realistic Mathematical Approach (PMR) on Learning Outcomes of Traveling Materials Build Flat Class IV Sarirejo State Elementary School Semarang City - Fatmala, Garnis; Khoiri, Nur; Setianingsih, Eka Sari (Universitas Nusantara PGRI Kediri, 2019)
Based on school observations the teacher delivered the lesson using teacher-centered lecture methods which had a bad impact, there were still many students who only memorized the formula but did not understand the basic concepts on a flat building around. From the problem, the purpose of this study was to determine the effectiveness of realistic mathematical approaches to student learning outcomes around the class IV Sarirejo Elementary School Semarang City. This research is quantitative research using the design True Experimental Design in the form of the Pretest-posttest Control Group Design. The data analysis technique used the t-test on the posttest value, with the results of the study supported by static calculations after the mathematical learning process that increased student learning outcomes with the Realistic Mathematics Approach (PMR) in the experimental class and mathematics learning experienced a slight increase in the control class. it can be seen that the final condition of student learning outcomes is different. Through the t-polled test, variants prove that obtained count of 4.013> t table of 2,000 then Ho is rejected and Ha is accepted, meaning it can also be said The Effectiveness of the Realistic Mathematical Approach (PMR) Against Student Learning Outcomes Build Flat Class IV Sarirejo Elementary School Semarang City.